A System‐Wide Analysis Using a Senior‐Friendly Hospital Framework Identifies Current Practices and Opportunities for Improvement in the Care of Hospitalized Older Adults. Issue 11 (30th October 2014) - Wong, Ken S.; Ryan, David P.; Liu, Barbara A.
<x xml:space="preserve">Abstract</x> Older adults are vulnerable to hospital‐associated complications such as falls, pressure ulcers, functional decline, and delirium, which can contribute to prolonged hospital stay, readmission, and nursing home placement. These vulnerabilities are exacerbated when the hospital's practices, services, and physical environment are not sufficiently mindful of the complex, multidimensional needs of frail individuals. Several frameworks have emerged to help hospitals examine how organization‐wide processes can be customized to avoid these complications. This article describes the application of one such framework—the Senior‐Friendly Hospital (SFH) framework adopted in Ontario, Canada—which comprises five interrelated domains: organizational support, processes of care, emotional and behavioral environment, ethics in clinical care and research, and physical environment. This framework provided the blueprint for a self‐assessment of all 155 adult hospitals across the province of Ontario. The system‐wide analysis identified practice gaps and promising practices within each domain of the SFH framework. Taken together, these results informed 12 recommendations to support hospitals at all stages of development in becoming friendly to older adults. Priorities for system‐wide action were identified, encouraging hospitals to implement or further develop their processes to better address hospital‐acquired delirium and functional decline. These recommendations led to collaborative action across the province, including the development of an online toolkit and the identification of accountability indicators to support hospitals in quality improvement focusing on senior‐friendly care.